Effect of Salt Pretreatment on the Growth and Yield of Oryza sativa L. (cv. Dendang) under Saline Condition - Nindya Arini; Budiastuti Kurniasih; Sriyanto Waluyo (Faculty of Agriculture, Universitas Gadjah Mada jointly with PISPI, 2019)
Productivity of rice as staple food of Indonesia needs to be improved. One of the efforts is by utilizing saline area for agricultural land. Salinity can be a serious problem leading to a decrease in crop productivity. Plant adaptation under salinity is an alternative to lower the risk, which can be improved by seedling pretreatment. The experiment was conducted in Baros, Kretek, Bantul, Yogyakarta. The objective of this research was to determine the growth and yield response of rice cv. Dendang to the salt pretreatment at early stage. The experiment was arranged in completely randomized design. The treatments used were salt pretreatment and without salt pretreatment. The salt pretreatment increased K+ concentration, total dry matter, plant height and number of tillers. However, it decreased proline and Na+ concentration of leaf. There was no significant difference on the yield and yield component. Increasing EC values up to 8.35 dSm-¹ at generative phase reduced the rice ability to cope this level of salinity despite the application of salt pretreatment. The benefit of salt pretreatment was exhibited on rice grown under EC value 5 dSm-¹.